2013
DOI: 10.1115/1.4023289
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Goniometer for Use Intraoperatively in Total Knee Arthroplasty

Abstract: Intraoperative range of motion (ROM) assessment can be challenging during total knee arthroplasty (TKA) surgery. As computer assisted surgery is costly and not readily available to many surgeons, we have developed a simple, cost-effective intraoperative device to precisely measure knee flexion and extension. A simple knee goniometer system was constructed consisting of a digital level mounted to a base that rigidly attaches two standard needles. The needles are pushed through the overlying soft tissue of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Of the 32 articles in the study, 15 reported on technology that is non-image-based [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ] and will be included in this section. The distribution of the included studies based on the surgery target is illustrated in Figure 4 a, while Figure 4 b shows their distribution based on the surgery type.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 32 articles in the study, 15 reported on technology that is non-image-based [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ] and will be included in this section. The distribution of the included studies based on the surgery target is illustrated in Figure 4 a, while Figure 4 b shows their distribution based on the surgery type.…”
Section: Resultsmentioning
confidence: 99%
“…Out of those 15 articles, 6 focused on measurements from manual instruments [ 84 , 85 , 86 , 87 , 88 , 89 ], and 9 focused on inertial-based instruments [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ], encompassing IMU-, accelerometer-, gyroscope-, and magnetometer-based instruments. The results will be presented considering those subgroups and summarized in Table 5 and Table 6 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Xin1 implant positioning system, as introduced in [ 5 ], uses existing imaging modalities such as a C-arm to guide the surgeon in the 3D anatomical environment, where otherwise experience and strong spatial perception are required. The system was designed with simplistic thinking in mind to augment established workflows and overcome the common shortcomings of surgical navigation systems, such as complexity, setup and takedown efforts as well as high costs [ 7 ]. The Xin1 principle was abstracted and developed into various prototype application modules, as summarized in [ 5 ].…”
Section: Discussionmentioning
confidence: 99%